Vasculoprotective Role of Olive Oil Compounds via Modulation of Oxidative Stress in Atherosclerosis - Summerhill, Volha; Karagodin, Vasilyi; Grechko, Andrey; Myasoedova, Veronika; Orekhov, Alexander (Frontiers in Cardiovascular Medicine, 2018)
Available evidence supports the significant role of oxidative stress in the endothelial injury, and there is a direct link between increased oxidative stress and the development of endothelial dysfunction. Endothelial dysfunction precedes the development of atherosclerosis and subsequent cardiovascular disease (CVD). Overproduction of reactive oxygen species facilitates the processes, such as oxidative modification of low-density lipoproteins and phospholipids, reduction in the NOS-derived nitric oxide, and the functional disruption of high-density lipids that are profoundly involved in atherogenesis, inflammation and thrombus formation in vascular cells. Thus, under oxidative stress conditions, endothelial dysfunction was found to be associated with the following endothelial alterations: reduced nitric oxide bioavailability, increased anticoagulant properties, increased platelet aggregation, increased expression of adhesion molecules, chemokines and cytokines. In this review, we summarized the evidence indicating that endothelial damage triggered by oxidation can be diminished or reversed by the compounds of olive oil, a readily available antioxidant food source. Olive oil bioactive compounds exhibited a potent capability to attenuate oxidative stress and improve endothelial function through their anti-inflammatory, anti-oxidant and anti-thrombotic properties, therefore, reduce the risk and progression of atherosclerosis. Also, their molecular mechanisms of action were explored, that would help to establish the potential preventive and/or therapeutic alternatives to the pharmacological remedies available.